A CRITICAL ANALYSIS OF THE PROPOSED CODIFICATION OF THE DUTIES OF CORPORATE DIRECTORS (The Pretoria Student Law Review, 2021)
In pursuance of the rectification of perceived shortcomings in the common law duties of directors, including inter alia the confusion and uncertainty among prospective and current directors concerning the degree of skill expected of them while carrying out their functions, the Department of Trade and Industry prepared a discussion draft of a proposed new Companies Act for South Africa, which, in contrast with the previous Companies Act, spelled out the duties of corporate directors. Following the discussion draft, a new Companies Bill was introduced in June 2008 in the spirit of the February 2007 bill regarding directors’ duties. In this article I shall attempt to outline the new statutory duties and other relevant sections and explain these duties as they are found in the Companies Bill. It should be stated that since the following discussion concerns proposed law not yet in force, no court decisions and very few academic articles are available to aid the interpretation thereof. The following interpretations are thus purely speculative and may differ from the ultimate interpretation that the court may give to these sections when applied. The interpretation of these sections can further not be aided by English statutory law, as the English statutory law only refers to fiduciary duties of directors and does not contain any specific criteria of care and skill by which a director’s conduct can be measured.
Keywords: common law; duties of directors; Department of Trade and Industry; new Companies Act; South Africa; new statutory duties; fiduciary duties of directors